THE FOUNDATION OF PARAGRAPH IN POETRY (TAMADDUN NURI JURNALI, 2025)
This article discusses the issue of paragraph and its study, as well as the occurrence of paragraph in poetic texts using examples. The place of paragraph not only in prose texts, but also in poetic texts is analyzed.